Subject and text production in virtual campus - Cuéllar Sánchez, Diana Mireya; Angarita Buitrago, Alfonso Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This research takes place in the context of academic processes in virtual campus, through field diaries, which recorded the interactions and dynamics of both students and teachers, two discussion groups were planned with counselors who develop their practice through virtual platforms. This allowed us to recognize a substantial difference between the usual subject of culture and the virtual subject, this aspect has been developed over the investigation. Finally an argument arises about the need to work with methodologies that blend the synchronous and asynchronous chnopedagogy practices of virtual environments in order to promote academic interaction, critical and the possibility of textual construction.